A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha: Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica - Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2021)
A new species of Myxia Bahder & Bartlett (Cixiidae: Cixiinae: Oecleini) is established as Myxia baynardi sp. n. collected from native palms in cloud forest habitat in Costa Rica. Placement in the genus Myxia is supported by molecular analysis of the cytochrome c oxidase subunit I (COI) and 18S loci as well as morphological characters. Haplaxius delta (Kramer) was collected along the Caribbean coast as a new country record for Costa Rica. Based on morphological characters observed and molecular analysis of COI and 18S, H. delta is herein moved to the genus Myxia.